Effect of Animated Video Media Therapy on Enhancing University Students’ Learning Motivation - Mah’ruf Todi Prihantoro; Zarir Abiyuda Pratama; Suparmi Suparmi (International Journal of Counseling and Psychotherapy, 2025)
Background: The use of animated media in education has gained popularity due to its potential to engage university students and simplify complex concepts. However, its impact on learning motivation remains underexplored, particularly in higher education contexts. Objective: This study aims to examine the effect of animated media on student learning motivation, specifically investigating how its use influences motivation in an academic setting. Method: The research involved 79 university students from the Educational Technology program at Universitas Sebelas Maret, selected through random sampling. Two variables were tested: the use of animated media (independent variable) and learning motivation (dependent variable). A questionnaire was used as the research instrument, and its validity, reliability, and normality were tested. Results: The analysis revealed that all instrument items were valid (r calculated > r table) and reliable (Cronbach’s alpha > 0.6), with the data showing a normal distribution (p = 0.194 > 0.05). Regression analysis revealed that animated media had a significant influence on learning motivation, accounting for 78.2% of the variation (R-squared = 0.782). The F-value of 120.960 and significance of 0.000 (< 0.05) confirmed the reliability of the model. Conclusion: Animated media significantly enhances learning motivation, particularly in explaining abstract concepts. However, challenges related to animation creation skills and access to technology need to be addressed. Contribution: This study offers educators valuable insights on how to incorporate animated media to enhance learning motivation effectively.